Restored to our destiny : eschatology and the image of god in herman bavinck's reformed dogmatics. - Mattson, Brian G. (Studies in Reformed Theology, 2011)
A close conceptual analysis of Herman Bavinck's (1854-1921) four-volume Reformed Dogmatics, this book explores what is broadly understood as the central motif of his work, the "organic" relationship between nature and grace, and highlights an overlooked aspect to this motif. Bavinck's view of nature and grace is not only rooted in his Trinitarian theology, but, more importantly, in his covenant theology. Exploring Bavinck's link between the doctrine of the imago Dei to an eschatology uniquely provided by Reformed covenant theology, this book serves to illumine the rationale behind his signature dogma that "grace restores and perfects nature." Given the link between the nature/grace motif and covenant theology, this book raises the question whether the one can stand without the other.